2020
DOI: 10.21203/rs.3.rs-27559/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Pandemic- Knowledge, Perception, Anxiety and Depression Among Frontline Doctors of Pakistan

Abstract: BackgroundCOVID-19 is a global pandemic and has become a major public health burden worldwide. With already fragile healthcare systems it can have long lasting effects in developing countries. Outbreaks especially a pandemic situation evokes fear related behaviors among healthcare professionals and there is always an increased risk of mental health disorders. Therefore, this study aims to determine knowledge and perception about this pandemic, prevalence and factors associated with depression/ anxiety among fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
6
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 11 publications
8
46
6
5
Order By: Relevance
“…According to the results of this study, females have more anxiety as compare to males which are in agreement with the outcome of other studies (37,38). Moreover, the results of different studies performed in Pakistan to analyze the anxiety levels of HCPs are in accordance with the finding of the current study (27,39). On the other hand, we have also noticed that the level of anxiety among the pharmacist is less as compared to medical doctors, dentists, and nurses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the results of this study, females have more anxiety as compare to males which are in agreement with the outcome of other studies (37,38). Moreover, the results of different studies performed in Pakistan to analyze the anxiety levels of HCPs are in accordance with the finding of the current study (27,39). On the other hand, we have also noticed that the level of anxiety among the pharmacist is less as compared to medical doctors, dentists, and nurses.…”
Section: Discussionsupporting
confidence: 91%
“…We analyzed that more than 95% of the HCPs of Pakistan are under the category of moderate level of anxiety to a severe level of anxiety. A study recently conducted in Pakistan has demonstrated similar findings (29).…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, the results of different studies performed in Pakistan to analyze the anxiety levels of HCPs are in accordance with the nding of the current study (27,39). On the other hand, we have also noticed that the level of anxiety among the pharmacist is less as compared to medical doctors, dentists, and nurses.…”
Section: Discussionsupporting
confidence: 89%
“…We analyzed that more than 95% of the HCPs of Pakistan are under the category of moderate level of anxiety to a severe level of anxiety. A study recently conducted in Pakistan has demonstrated similar ndings (29).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation